Evaluating passive physiological data collection during Spravato treatment - Todd M. Solomon; Matus Hajduk; Martin Majernik; Jamileh Jemison; Alexander Deschamps; Jenna Scoggins; Adam Kolar; Miguel Amável Pinheiro; Peter Dubec; Ondrej Skala; Owen Muir; Amanda Tinkelman; et al. (Frontiers Media S.A., 2023)
Spravato and other drugs with consciousness-altering effects show significant promise for treating various mental health disorders. However, the effects of these treatments necessitate a substantial degree of patient monitoring which can be burdensome to healthcare providers and may make these treatments less accessible for prospective patients. Continuous passive monitoring via digital devices may be useful in reducing this burden. This proof-of-concept study tested the MindMed Session Monitoring System™ (MSMS™), a continuous passive monitoring system intended for use during treatment sessions involving pharmaceutical products with consciousness-altering effects. Participants completed 129 Spravato sessions with MSMS at an outpatient psychiatry clinic specializing in Spravato treatment. Results indicated high rates of data quality and self-reported usability among participants and health care providers (HCPs). These findings demonstrate the potential for systems such as MSMS to be used in consciousness-altering treatment sessions to assist with patient monitoring.